Oral Pyogenic granuloma: Retrospective Review of 49 Cases in a Tertiary Care Dental Institution of Odisha - Ipsita Mohanty; Swagatika Panda; Neeta Mohanty; Radhaprasanna Dalai; Sreepriti Champatyray; Priyanka Sukla (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pyogenic granuloma (PG) also known as “Lobular capillary hemangioma,” appears as an overgrowth oftissue due to irritation, physical trauma, or hormonal changes in the oral cavity. this present study is on aseries of cases comprising of 49 cases of pyogenic granuloma is the first of its kind reported from EasternIndia. Even though patients usually do not report the hospital for pyogenic granuloma unless the lesionis large and incapacitating, such number in four years is not very less. Therefore it may be deduced thatpyogenic granuloma is not rare in this part of India.